Factor affecting customer intention to buy street food in Kuala Terengganu / Ahmad Irfan Badrul Hisyam and Muhammad Afiq Dhiyaulhaq Mark Sharizal - Badrul Hisyam, Ahmad Irfan; Mark Sharizal, Muhammad Afiq Dhiyaulhaq (2021)
This research is to study about the factor affecting customer intention to buy street food in Kuala Terengganu. Our research information can help people to are selling at food at street can improve their selling with known to target what the customer want. Next is our research objective is to examine factor influence customer intention to buy street food and to evaluate customer preference on street food. The data will collect in Kuala Terengganu and the target of the respondent the teenagers.